Alevism in Turkey and in Transnational Space: Negotiated Identities between Religion, Culture and Law (Stato, Chiese e pluralismo confessionale, 2020)
SUMMARY: 1. Introduction - 2. Alevi Population in Turkey and in Europe - 3. What is Alevism? Who are the Alevis? - 4. Discrimination against Alevis and Alevi Massacres from the Ottoman Empire to the Turkish Republic - 5. Alevi Migration in Turkey and to Europe - 6. Alevi Organizations in Europe: Cultural, Social, and Historical Perspectives - 7. Discourses of “Other” vs “Equal” on Alevis - 8. Alevi Associations in Europe: Legal Perspectives - 9. Alevism in the Turkish Legal Setting - 10. Alevism at the European Court of Human Rights - 11. Concluding Remarks on Legal Issues - 12. Concluding Remarks on Social and Cultural Issues.ABSTRACT: Using interdisciplinary lenses, this article examines the cultural, social, and juridical status of the Alevis in Turkey and Western Europe. The ongoing social exclusion and discrimination against Alevis in Turkey make their everyday lives challenging. In Europe, Alevis organized themselves in associations, forming vibrant transnational communities. They struggled for recognition of their cultural-religious rights, and in some European countries, they are given special status. As we will illustrate, their recognition in Europe significantly effected in their case in Turkey but failed to emancipate them fully and posed further issues to tackle with and for the Alevis in Turkey. Gedik and Birkalan-Gedik present sociological, historical, and political contexts to understand the current realities of Alevis in Turkey and Europe, mostly based on their ethnographic studies. Madera examines five cases between 2007-2016 which were presented by the Alevis to the European Court. We conclude that currently, Turkey does not try to suffice the European requirements, namely, the implementation of policies aimed at guaranteeing adequate protection of the collective dimension of religious freedom in a way consistent with European directives.